Nghiên cứu tổng hợp và cấu tạo một số 4,5-đinitro pyrazol chứa dị vòng O, S - Triệu, Nguyễn Đình; Hà, Vũ Văn (Vietnam Journal of Chemistry, 2012)
By condensation of furfural or thiophen-2-carboxaldehyde with aryl methyl ketone have been synthesized a,b-unstaturated ketones. These ketones can be reacted with arylhidrazines to form heterocylic 4,5-dihydropyrazoles. These products was confirm by IR, 1H-NMR and 13C-NMR. The charge densities on the carbon atoms of the main molecular skelete of the substituted 4,5-dihydropyrazoles have been computed using chemical quantum AM1.